Outcomes of Percutaneous Cross K-Wire Fixation for the Management of Supracondylar Displaced Fractures of Elbow in Children - Akhtar Hussain, Ahmadzeb, Shehriyar Khan, Farmanullah Khan, Abbas Khan, Khalid Wazir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It is estimated that about 16–17 percent of all fractures in pediatric patients are supra-condylar fractures of the elbow. Different techniques are used for the management of supracondylar displaced fractures of elbow in children. Objective: To find out the outcomes of percutaneous cross- K-wire fixation for the management of supracondylar displaced fractures of elbow in children Methodology: This descriptive cross sectional study was carried out at Orthopedic Department of Khyber Teaching Hospital Peshawar for duration of one year from June 2021 to July 2022. A total of 80 patients were included in the current study. All the patients were followed for up to six months. At last follow-up, all patients were evaluated using Flynn’s criteria. All the data analysis was done by using IBM SPSS version 23. Results: On the basis of Flynn’s criteria, excellent results were observed in 54 (67.5%) patients, good results in 20 (25%) patients, fair results in 4 (5%) patients while poor results were observed in 2 (2.5%). Based on the post-operative associated problems, pin-tract infections were observed in 7 (8.75%) patients, cubitus varus deformity was observed in 2 (2.5%) and temporary ulnar nerve deficit was observed in 5 (6.25%) patients. Conclusion: Our study concludes that in children, type-II & III supra-condylar displaced fracture of elbow can be managed easily and effectively with a low rate of complications. Keywords: Percutaneous cross- K-wire fixation; Supracondylar displaced fractures; Elbow